2021
DOI: 10.1111/tpj.15620
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic acid‐modified xylan side chains and their cross‐linking products in rice cell walls are reduced in the Xylosyl arabinosyl substitution of xylan 1 mutant

Abstract: The intricate architecture of cell walls and the complex cross-linking of their components hinders some industrial and agricultural applications of plant biomass. Xylan is a key structural element of grass cell walls, closely interacting with other cell wall components such as cellulose and lignin. The main branching points of grass xylan, 3-linked L-arabinosyl substitutions, can be modified by ferulic acid (a hydroxycinnamic acid), which cross-links xylan to other xylan chains and lignin. XAX1 (Xylosyl arabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…Previous studies of rice GT61 members showed that eight of them, including OsXAT2–OsXAT7, OsXYXT1, and OsXAX1, mediate 3‐ O ‐Ara f , 2‐O‐ Xyl, and hydroxycinnamate‐esterified 3‐ O ‐Ara f substitutions of xylan, respectively (Anders et al., 2012; Chiniquy et al., 2012; Zhong, Cui, Phillips, & Ye, 2018; Zhong et al., 2021; Feijao et al., 2022). Whether any of the remaining rice GT61 members are involved in xylan substitutions remains elusive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of rice GT61 members showed that eight of them, including OsXAT2–OsXAT7, OsXYXT1, and OsXAX1, mediate 3‐ O ‐Ara f , 2‐O‐ Xyl, and hydroxycinnamate‐esterified 3‐ O ‐Ara f substitutions of xylan, respectively (Anders et al., 2012; Chiniquy et al., 2012; Zhong, Cui, Phillips, & Ye, 2018; Zhong et al., 2021; Feijao et al., 2022). Whether any of the remaining rice GT61 members are involved in xylan substitutions remains elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Grass xylan is heavily substituted with 3‐ O ‐Ara f side chains, some of which can be further decorated at O ‐2 with Xyl or Ara f . Although an early study suggested that rice XAX1 was likely responsible for Xyl transfer onto the Ara f residues of xylan to generate the Xyl‐Ara f side chains (Chiniquy et al., 2012), a recent report proposes that XAX1 functions to transfer hydroxycinnamate‐esterified Ara f residues onto xylan based on the finding that the xax1 mutant has a general reduction of hydroxycinnamate‐esterified Ara f residues in xylan regardless of whether Ara f is substituted with Xyl or not (Feijao et al., 2022). Therefore, glycosyltransferases involved in the transfer of Xyl or Ara f onto the 3‐ O ‐Ara f residues of xylan to form the Xyl‐Ara f and Ara f ‐Ara f disaccharide side chains remain elusive (Zhong et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study focused on the maize grain fraction resistant to mild acid pretreatment and subsequent enzymatic saccharification found that feruloylated oligosaccharides made up 39% of the enzyme-resistant oligosaccharides, and most of these feruloylated oligosaccharides contained either the complex, feruloylated trisaccharide side-chain FAXG (α- l -galactopyranosyl-(1 → 2)-β- d -xylopyranosyl-(1 → 2)-5- O - trans -feruloyl- l -arabinofuranose; see Figure 1 ) or the feruloylated disaccharide FAX (β- d -xylopyranosyl-(1 → 2)-5- O - trans -feruloyl- l -arabinofuranose; see Figure 1 ) side-chains ( Appeldoorn et al, 2013 ). Because more complex AX structures contain additional glycosidic linkage types compared to simple AX ( Feijao et al, 2022 ), more elaborate enzymatic machinery is needed to break down these complex AX ( Rogowski et al, 2015 ; Beri et al, 2020 ). Unique microbial growth and fermentation patterns thus arise from different AX based on which microbial population is best equipped to compete for energy from the AX food source, i.e., produce the enzymes needed to break down the polymer into fermentable monosaccharides ( Yang et al, 2014 ; Centanni et al, 2017 ; Mendis et al, 2018 ; Ndeh and Gilbert, 2018 ).…”
Section: Introductionmentioning
confidence: 99%